The Effectiveness of Solution-Focused Brief Career Group Counseling to Reduce Student Career Indecision - Budi, Leo Setya; Puji Sugiharto, Dwi Yuwono; Sunawan, Sunawan (Jurnal Bimbingan Konseling, 2021)
Career indecision is the difficulty faced by individuals in making decisions about career, work, and further education. This study examines the effectiveness of solution-focused brief career counseling group counseling to reduce career indecision for vocational high school students. Using this type of experimental research with pretest-posttests random control group design. The research subjects involved 12 students: the experimental group (6 students) and the control group (6 students). The effectiveness of counseling was assessed by changing the pretest and post-test results on students. To measure the level of career indecision assessed using the Career Decision-making Difficulties Questionnaire (CDDQ). Stages of group counseling solution-focused brief focus career counseling in the counseling process; Pre-session change, Relationship development, Problem Clarification and Goal setting; Miracle Question, Scale for goal setting, incorporating systems thinking; Constructing meaningful homework, Write down all the strengths of the client & evaluation. The results showed that the solution-focused brief career counseling group effectively reduced students' career indecision. The implications of the findings of this study are discussed in the article.